The University of California Pay It Forward Open Access Publishing Research Project: An Interview with MacKenzie Smith. Issue 1 (4th July 2017) - Cook, Eleanor I.; Smith, MacKenzie
ABSTRACT: In 2014, University of California, Davis University Library and the California Digital Library collaborated on an Andrew W. Mellon Foundation grant-funded project to explore costs associated with moving scholarly journal subscriptions in the U.S. market entirely to an Article Processing Charge business model, known also as "Gold Open Access." We contacted MacKenzie Smith, one of the principal investigators, in order to get her reflections on the process of gathering the data, and to discuss some implications of the findings. The interview suggests that the "Pay It Forward" model could be successful over time, following a necessarily complex transition period.